Sowing the seeds of love: Ovid's Sementivae (Fasti 1.655-704) - Armstrong, RM (Oxford University Press, 2024)
The Sementiuae, one of very few feriae conceptiuae (movable feasts) mentioned in the Fasti, is the one most overtly and playfully framed as being out of place within this poem of fixed dates. The festival’s intrusion offers an opportunity for the poet to continue his oblique reflections on the meaning of time in the agricultural context and the mixing of nature and culture it entails. Yet, while the time to sow belongs to wider cycles of annual recurrence, the description of the festival itself is pointedly woven into the linear progressions of allusion, most markedly to the Georgics and Tibullus 2.1. In the gaps between the composition of these central intertexts and the emergence of the Fasti, literary time has passed, and so too has the political situation shifted; Ovid can now both update and reignite Vergilian and Tibullan debates on the moralities of agriculture and war in the context of Augustan Peace and Concordia. Meanwhile, he also modifies and subtly reconfigures the relationship between Ceres and Tellus in a manner not found in either of his dominant poetic influences. Thus, throughout his account of this celebration of the sowing of grain, Ovid simultaneously highlights its lack of fixity and offers a variety of ways by which to anchor it both within the poem and within Roman literary and religious culture more widely.